Investigating the effect of urban governance on urban resilience (Case study: Tehran) - Gholam Reza soroushan; Abdallah hendiani; parvane zivyar pardei; Ali tavakolan (تحقیقات کاربردی علوم جغرافیایی)
In recent decades, the issue of resilience has become a specialized and public issue in society. Concepts of resilience in urban communities, which is in fact an action against development at the national level and purely physical development on an urban scale, and an attempt to achieve qualitative standards in the field of urban planning. In the meantime, the issue of resilience in urban communities means that society is able to withstand severe natural disasters without major damage, injury, production stoppage and reduced quality of life, and also at the superficial level, the goal of resilience as an ideal. The world is at the individual, organizational and community level. The aim of this study was to investigate the effect of urban governance on urban resilience. This research is applied in terms of purpose and descriptive-analytical in terms of method. The statistical population of the study consisted of citizens living in Tehran and experts in the field of research. The sample size was estimated for the statistical group of citizens using Cochran's formula 384 people and for specialists 60 people. In order to analyze the information and achieve the research objectives, structural equation modeling in LISREL software environment was used. Findings of this study showed that urban governance has a direct effect on urban resilience so that 0.42% of the variance of urban resilience variable can be explained by urban governance.